(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Fast dissolving oral films are a relatively new drug delivery technology with the potential to improve patient adherence by increasing the safety and effectiveness of the therapeutic molecule. The film may be put on the tongue’s roof or underside for an effective medicine delivery method. This film instantly dissolves when placed on the tongue, releasing the medication into the saliva. Saliva travels down the oesophagus and into the stomach, where certain medications are absorbed. The drug’s bioavailability is improved, and there’s no danger of choking, and the pill feels great in the mouth. The inability to swallow pills, capsules, etc., quickly dissolves this barrier to medicine administration. Fast dissolving oral films are discussed in this review article along with their oral mucosa, formulation components, a technique of fabrication, an assessment, and potential future applications.